УКРАЇНОЗНАВЧІ НАУКОВІ УСТАНОВИ В США (друга половина ХХ ñ початок ХХІ ст.) (Zaporizhzhia Historical Review, 2021)
The Ukrainian research institutions in USA during the second half of the 20th ñ the beginning of the 21st century are studied. The scientific activities of the institutions are reconstructed in details. The contribution between Ukrainian and American scholars is described.